2016
DOI: 10.1007/s11010-016-2805-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of serum levels of microRNA-21 and matrix metalloproteinase-9 in patients with acute coronary syndrome

Abstract: Acute coronary syndrome (ACS) is one of the leading causes of cardiovascular death. It seems that microRNA-21 and matrix metalloproteinase-9 implicated in the pathogenesis of cardiovascular diseases. The aim of this study was to investigate the role of circulating miR-21 and MMP-9 as biomarkers for ACS. Based on coronary angiography and electrocardiography results, 50 patients with ACS and 50 patients with stable coronary artery disease (stable CAD) were enrolled in this study. Samples were collected from pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 53 publications
0
12
0
1
Order By: Relevance
“…In a study of subclinical atherosclerosis, plasma miR-21a levels were positively correlated with systolic, diastolic blood pressure, CRP and cIMT, but negatively correlated with nitric oxide (NO) and eNOS [ 31 ]. Similarly, in acute coronary syndrome, miR-21 levels were increased and correlated with CRP, age and visfatin, but negatively correlated with HDL-cholesterol [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a study of subclinical atherosclerosis, plasma miR-21a levels were positively correlated with systolic, diastolic blood pressure, CRP and cIMT, but negatively correlated with nitric oxide (NO) and eNOS [ 31 ]. Similarly, in acute coronary syndrome, miR-21 levels were increased and correlated with CRP, age and visfatin, but negatively correlated with HDL-cholesterol [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) were considered as novel potential biomarkers in the detection of ACS (Ahlin et al, 2016). Recently, increasing evidence has been indicative of the diagnostic and prognostic value of miRNAs in ACS (Darabi et al, 2016;Wei et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating miR-21 in patients with ACS was significantly higher than that in patients with stable coronary heart disease/non-ACS [15,39,40], and it was also found that miR-21 was associated with visfatin [39] and mmp-9 (mmp-9) [40], which may participate in the pathogenesis of ACS by jointly promoting inflammatory response [39]. When miR-21 was combined with miR-1 and miR-499, the diagnostic efficiency was significantly improved (AUC 0.94), which was superior to the hypersensitive troponin T (AUC 0.89) [15].…”
Section: Resultsmentioning
confidence: 99%